Creatine and glycerol hyperhydration in trained subjects before exercise in the heat - Easton, C.; Turner, S.; Pitsiladis, Y. P. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
The authors examined the effects of combined creatine (Cr) and glycerol (Gly) supplementation on responses to exercise in the heat. Subjects (N = 24) were matched for body mass and assigned to either a Cr or placebo (Pl) group. Twice daily during two 7-d supplementation regimens, the Cr group received 11.4 g of Cr·H2O and the Pl group received 11.4 g of glucose. Subjects in both groups also ingested 1 g of Gly/kg body mass (twice daily) in either the first or the second supplementation regimen. This design allowed 4 possible combinations of supplements to be examined (Pl/Pl, Pl/Gly, Cr/Pl, and Cr/Gly). Exercise trials were conducted pre- and postsupplementation at 30 °C and 70% relative humidity. In the Pl group, total body water (TBW) increased by 0.50 ± 0.28 L after Gly and in the Cr group by 0.63 ± 0.33 L after Pl and by 0.87 ± 0.21 L after Gly. Both Cr/Pl and Cr/Gly resulted in significantly attenuated heart rate, rectal temperature, and perceived effort during exercise, although no regimen had any effect on performance. The addition of Gly to Cr significantly increased TBW more than Cr alone (P = 0.02) but did not further enhance the attenuation in HR, Tre, and RPE during exercise. These data suggest that combined Cr and Gly is an effective method of hyperhydration capable of reducing thermal and cardiovascular responses.